Effects of sewage pollution on the structure of rocky shore macroinvertebrate assemblages - Cabral-Oliveira, J. (2014)
The urgency to find efficient indices and indicators to prevent further deterioration of coastal areas is one of the hot topics in today’s scientific publication. However, a detailed knowledge of community responses to anthropogenic impacts is essential to sustain those indices. The studies on the response of benthic community to sewage pollution on intertidal rocky shores are generally based on visual census and do not take into account the tidal levels. In order to fulfil this gap in this study: (i) the sampling was performed by destructive sampling, with all individuals identified to the species level; (ii) the samplingwas done at all levels of the intertidal (sublittoral fringe, eulittoral, and littoral fringe). Sewage pollution changed the environmental variables and the abundance of macroinvertebrates, being Mytilus galloprovincialis, Melarhaphe neritoides, and Chthamalus montagui the species most responsible for the dissimilarities observed. Effects were different on the three intertidal zones: community structure changed in the sublittoral fringe; suspensionfeeders abundances and species richness increased in the eulittoral; no differences were detected in the littoral fringe. Moreover, the results confirm that the presence of sewage discharges tended to benefit suspension feeders, and that the sensitive species were replaced by opportunistic ones.